Multimodal Analysis In Wardah Islamic Beauty Product Advertising - Ririn Fitri Suryani; T. Silvana Sinar; T. Thyrhaya Zein (International Journal of Educational Research & Social Sciences, 2021)
This study discusses multimodal analysis in advertising Wardah Islamic beauty products. This time, beauty advertising is one of the various types of advertising in the mass media, which certainly covers people's lives today. It is a multimodal discourse in which text consists of complex sources of meaning. The complexity of meaning is caused by the messages conveyed in advertisements do not only use verbal language but also visual images that work together as a unified meaning. This study observes wardah beauty advertisements manifesting verbal and visual elements. This study uses Bahasa Halliday Metafunction component (2004) and multimodal discourse analysis proposed by Kress and Van Leeuwen (2006). The result shows that, found meaning contained in verbal texts and visual texts in Wardah beauty advertisements in the form of the experiential function of verbal texts includes processes: material, mental, relational, behavioral, verbal and tangible. Participants: gold, actor, senser, behavior, phenomenon, speaker, speech, form and value. Circumstantial: method, time, location, cause and accompaniment. Representation Metafunction, Interpersonal Metafunction, and Realization of visual text and verbal text in Wardah's beauty advertisement which is verbalized by a narrator along with Visual advertisements that appear by exploring the relationship of linguistic elements to visual images which are the fabric of messages, goals and intentions of producers to the audience.